Remote monitoring technology and servitization: Exploring the relationship - Grubic, Tonci (Computers in industry, 2018)
•Paper explores benefits of Remote Monitoring Technology (RMT) and how they support servitization.•An exploratory multiple-case study of four manufacturing companies was conducted.•The research makes three contributions. Remote Monitoring Technology (RMT) is recognised as one of the key enablers of servitization. While servitization has been the subject of intense research for years, the role of RMT therein has been less explored. This paper aims to contribute to this important topic by addressing the following research questions: what are the benefits of RMT and how do they support servitization? An exploratory multiple-case study of four manufacturing companies, operating in aerospace, industrial equipment, marine, and transportation sector, was conducted. The research makes three contributions. Firstly, it is the first systematic study of the benefits of RMT and their role in servitization. Secondly, it recognises the centrality of the RMT challenge for the relationship between RMT and servitization. Finally, it explores the implications of the RMT challenge for this relationship. Three implications have been identified, which suggest a novel perspective on the nature of RMT, RMT-enabled services, and their role in servitization.